Hubungan Status Gizi dengan Proses Penyembuhan Luka pada Pasien Post Apendektomi - Andi Siswandi; Mardheni Wulandari; Mizar Erianto; Azahrah Mawaddah Noviska (Puslitbang Sinergis Asa Professional, 2020)
Appendicitis is part of the emergency cases that often occur in the abdominal area. Appendicitis is a prototype disease that takes place through inflammation due to obstruction and ischemia with the main symptoms which is pain that reflects the state of the disease. Appendicitis requires surgical appendectomy to reduce the risk of perforation. Apendectomy surgery is one type of wound that is an incision wound. The time of wound healing can be determined by the distinguishing between types of acute or chronic wounds. Appendectomy that does not have a post-surgical infection is categorized as an acute wound, physiologically the acute wound will heal ± 0-21 days. However, if the provision of nutrition is not fulfilled properly it will be almost the wound healing process. One factor that can influence the wound healing process is nutritional status. This study aim to determine the correlation of nutritional status with the wound healing process of post-appendectomy patients in RSUD Dr. H. Abdoel Moeloek, Bandar Lampung. This study used observational analytic with cross sectional approach. The sampling technique used was accidental sampling. The data were analyzed by using Chi-square test. From the Chi-square test found a relationship of nutritional status with a significant wound healing process (p <0.05) which is obtained p = 0.004, and the value obtained (OR = 10.5) can be said that adequate nutritional status is 10.5 times more likely to experience good wound healing when compared to undernourished nutritional status. There is a correlation between nutritional status and wound healing process in post-appendectomy patients.